(3TQM GdHgGFjI aj GdMSGHs - (3GdeGFj GdLdj, GHf GdeGA, YeQ Hf CMeOs
(3ChdgG (B:s
(3jG ef YLR Yf LejY JVGYa fYeg CbdGe CagGe GdYbdGA Efj QSeJ ajeG eVi aj CjGe GdJMUjd hCKfGA GdJOQjS aj GdJYWjd JYdjbGJ Ydi GdehGVY GdeTcdI hTHgGJ Ydi QehR GdeHGMK GdeaUdI s
(3BNQgG (B:s
(3bhdg hHYO ESbGW GdeTJQc hgh GdNeSI hGdYTQhf hGdeGd ef GdWQajf jHbi aj GdWQa GdChd YTQI CTjGA eYGOdI dNeSI hSHYjf aj GdWQa GdBNQ hgh GdeSCdI GdChdi Jes
(3JHUQI GdYfhGf (B:s
(3TQM GdNdGUI aj GdMSGH dHgGA GdOjf GdYGedjs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdQjGVjGJs